Trickle-Down Economics' Arthur Lewis Fails: an economic development study of Mount Bromo in Ngadisari Village, Sukapura District, Probolinggo Regency, East Java - Puspitarini, Renny Candradewi; Anggraini, Isrofiatul (Journal of Indonesian Tourism and Development Studies, 2019)
In this paper, we will examine if the trickle-down effect has ever taken in rural Indonesia. One of the cases draws attention in economic development study is poverty and income gap from wealthiest people to the less fortunate larger group of people. The argument goes as trickle-down effect appears to be the best solution to eradicate poverty as well as to solve the income gap. Tourism has become a strategy targeted by the government to spread the trickle-down effect to the less fortunate larger group of people. The government believes by sustaining the growth in tourism would accelerate the trickle-down effect and brings a less fortunate group of people to better living. In its fundamental theory, the trickle-down effect has offered delusion where jobs would be created as the conditions are met. However, this paper argues that even in tourism the trickle-down effect strategy has served less for what it has promised. Through qualitative research in Ngadisari Village, a remote area, where Mount Bromo has been a tourism landmark globally, this paper finds that trickle-down effect has come with little benefit to uplift the living standard of the poor. Thus, the trickle-down effect has served only as delusions of growth government has ever aspired.Keywords: humanism, Mount Bromo, tourism economics, tourist destination, trickle-down economics.